(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Culture is a set of symbolic devices and works that define human activity and the importance of this activity. Culture can be manifested in activities such as music, literature, visual arts, architecture, theater, cinematography, and lifestyle. In anthropology, the term “culture” refers to products and their production, aesthetic meaning, and social relations connected to these processes. In this sense, culture includes art, science, and spiritual systems